Investigation of Health Literacy Levels of Inpatient Companions in Terms of Socioeconomic Differences and Some Health Behaviors (Turkey Health Literacy Journal, 2025)
The factors that influence health literacy are of significance both on a global scale and within the national context. The present study examines the relationship between the health literacy levels of companions and their socio-economic status and healthy lifestyle behaviours. The study is descriptive in nature and consists of caregivers of patients hospitalised at a university hospital. The data were collected using the Turkish version of the European Health Literacy Scale (ASOY-TR), a questionnaire form to assess individuals’ socio-economic status, and the International Physical Activity Questionnaire (IPAQ) Short Form. The data presented herein were collected by the researcher through the implementation of face-to-face interviews, which took place during the subjects’ visits to the institution. The statistical analyses encompassed a range of methods, including counts, percentages, chi-square tests, and binary logistic regression analyses. The correlation between age and health literacy levels is negative; that is to say, as individuals grow older, their capacity to comprehend health-related information and make informed decisions about their own health diminishes. Conversely, individuals who possess both a high socio-economic status (SES) and good general health have been shown to have higher levels of adequate health literacy. Individuals who have never smoked exhibited lower health literacy compared to those who had ceased smoking, while those who currently consume alcohol demonstrated similarly deficient health literacy as those who had ceased.